Evaluasi Tingkat Kejenuhan Terminal Building Bandar Udara Hang Nadim Batam - M Nurmandra Muas; Ari Sandhyavitri; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The number of passengers of Hang Nadim Airport Batam is experiencing saturation so that it is necessary to develop the passenger terminal against existing regulations. It is known that in 2015 the number of passengers reached 5.20 million passengers and this already exceeded the passenger capacity planned earlier in 2008, which was 5 million passengers with a passenger terminal area of 30,677 m2. The method for knowing the available capacity can now be developed or not using the airport operational utility level method, the data used are advanced survey data, the largest annual passenger, and busy passenger on numbers. In planning, development there are two types of equations used, namely is simple linear regression and the multiple linear regression, where the non-independent variable data is the recapitulation of air transport data from 2007 to 2016 in the form of aircraft, passenger and cargo movements while the independent variable is population data, domestic products gross regional, and per capita income. The relationship between non-free variables and independent variables is very strong so it can be processed using the SPSS computer program to obtain the equation analysis model. The need for building terminal development for the next 10 years, 2017 to 2026 aims to expand terminal building, passenger capacity, and passengers during busy times. The results of the terminal building development plan during the planned year are 2026 covering an area of 59,079 m2 with a passenger capacity reaching 9,481,174 people which can accommodate 2,430 people during a passenger rush hour.Keywords: Saturation, Passenger, Capacity, Development